Sertipikat Tanah VS Sertifikat Tanah: Analisis Data Penggunaan Istilah Produk Hukum di Media Sosial - Ridho Darman (STIKes Ibnu Sina Ajibarang, 2024)
The land title (in Indonesian: sertipikat) is a legal product issued by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, while “sertifikat” (spelled with 'f' instead of 'p'), which is the standard term according to KBBI (Indonesian Dictionary). The number of social media users increases every year, resulting in a growing amount of data generated. Big data derived from social media can encompass public perception or societal behaviors. The significant benefits derived from social media analytics provide opportunities to explore and analyze data sources within social media. This study analyzes data from the social media platforms Twitter, Facebook, and Instagram to determine common terms used by the public regarding